THE EFFECTS OF DIFFERENT LEVELS OF DIETARY PROTEIN AND LIPID ON THE GROWTH OF RED SNAPPER, Lutjanus sebae - Nyoman Adiasmara Giri; Ketut Suwirya; Muhammad Marzuqi; Ni Wayan Widya Astuti (Indonesian Aquaculture Journal, 2009)
Red snapper, Lutjanus sebae is favored in mariculture activities because it has a relatively good market and price. Technology for big scale seed production of this species has been developed and is now adequate to supply seed for grow-out activities. However, the availability of artifical diets for L. sebae is still a major constraint for grow-out production. Data on optimum dietary protein and lipid requirements for this fish as a basic information in feed development is not available yet. The objective of the present study was to find out dietary protein and lipid requirements for juvenile of L. sebae. A 70-day feeding experiment was conducted in 24 fiberglass tanks, 200 L volume. Each tank was equipped with a flow-through water system. Twenty five hatchery-produced juveniles of L. sebae (43.1 g BW) were randomly selected and stocked in each tank. The fish were fed with the experimental diets twice everyday at a level of 3% of biomass for the first 4 weeks, and then 2% of biomass afterward. Twelve experimental diets were prepared in form of dry pellet containing casein and fish meal as the main protein sources. Experimental diet had 4 levels of crude protein (32%, 37%, 42%, and 47%) and each protein level consisted of 3 levels of lipid (7%, 12%, and 17%). The experiment employed factorial method with completely random design using 12 combination treatments and 2 replications for each treatment. Result of the experiment showed that there was no significant effect of dietary protein and lipid on growth, feed consumption, and feed efficiency of tested fish. Growth and feed efficiency of fish fed on diet containing 42% and 47% crude protein were significantly higher than that of fish fed on diet containing 32% and 37% crude protein. High lipid content in the diet (17%) resulted in poor growth and poor feed efficiency. This data indicates that Lutjanus sebae has limited ability to utilize dietary lipid as an energy source. Result of the present study recommends that dietary protein and lipid requirement for good growth of L. sebae should be 42% and 12%, respectively.